The role of family and maternal factors in childhood obesity - Gibsone, L.; Byrne, S.; Davis, E.; Blair, E.; Jacoby, P.; Zubrick, Stephen (Australasian Medical Publishing Company, 2007)
Objective: To investigate the relationship between a child's weight and a broad rangeof family and maternal factors.Design, setting and participants: Cross-sectional data from a population-based prospective study, collected between January 2004 and December 2005, for 329 childrenaged 6 13 years (192 healthy weight, 97 overweight and 40 obese) and their mothers (n = 265) recruited from a paediatric hospital endocrinology department and eight randomly selected primary schools in Perth, Western Australia.Main outcome measures: Height, weight and body mass index (BMI) of children and mothers; demographic information; maternal depression, anxiety, stress and selfesteem; general family functioning; parenting style; and negative life events.Results: In a multilevel model, maternal BMI and family structure (single-parent v two-parent families) were the only significant predictors of child BMI z scores.Conclusion: Childhood obesity is not associated with adverse maternal or family characteristics such as maternal depression, negative life events, poor general family functioning or ineffective parenting style. However, having an overweight mother and a single-parent (single-mother) family increases the likelihood of a child being overweight or obese.